KEPATUHAN WAJIB PAJAK UMKM KABUPATEN KARO DITINJAU DARI PEMAHAMAN PENYUSUNAN LAPORAN KEUANGAN, INSENTIF PAJAK DAN PENGETAHUAN PERPAJAKAN - Yunita Eriyanti Pakpahan; Ewin Ginting (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this research is to test and analyze the compliance of MSME taxpayers in Karo Regency. The total population in this study was 10,440 MSMEs recorded at the Karo Regency Cooperative, Employment and MSME Service from the agriculture, industry, services and tourism sectors. A sample of 100 SMEs was determined using the Slovin sample size formula. The sampling technique used was simple and purposive random sampling technique. Data were analyzed using descriptive statistics. The conclusion obtained from this study is that the variables of understanding the preparation of financial statements and tax incentives have an effect on MSME taxpayer compliance. However, tax knowledge does not affect the compliance of MSME taxpayers in Karo Regency.